L’allégorie de la femme-enfant alias Gisèle Prassinos comme aporie de genre dans le surréalisme - Annie Richard (Itinéraires, 2012)
The organic link between automatic writing, surrealism’s subversive objective and the femme-enfant figure, produces a contradiction revealed by Man Ray’s photograph of the 1934 encounter between André Breton’s group and “Alice II,” as they named the young poetess Gisèle Prassinos. Such a mythological appellation, although proceeding from the modern objective approach to the world, in no way disrupts the traditional analogic structure of gendered identities and prevents the “Sublime Point” from evolving beyond the masculine/feminine opposition at the basis of binary thought.